2021
DOI: 10.3390/nu13072321
|View full text |Cite
|
Sign up to set email alerts
|

Food Enrichment with Glycyrrhiza glabra Extract Suppresses ACE2 mRNA and Protein Expression in Rats—Possible Implications for COVID-19

Abstract: Angiotensin converting enzyme 2 (ACE2) is a key entry point of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) virus known to induce Coronavirus disease 2019 (COVID-19). We have recently outlined a concept to reduce ACE2 expression by the administration of glycyrrhizin, a component of Glycyrrhiza glabra extract, via its inhibitory activity on 11beta hydroxysteroid dehydrogenase type 2 (11betaHSD2) and resulting activation of mineralocorticoid receptor (MR). We hypothesized that in organs such as t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 52 publications
(56 reference statements)
0
14
0
Order By: Relevance
“…Cinatl and colleagues found that glycyrrhizin was among the most active compounds tested in inhibiting replication of the SARS-CoV [ 12 ]. Thus, licorice and GA could be an old weapon against emerging diseases [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cinatl and colleagues found that glycyrrhizin was among the most active compounds tested in inhibiting replication of the SARS-CoV [ 12 ]. Thus, licorice and GA could be an old weapon against emerging diseases [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…In rat models, diets supplemented with 150 mg/kg/day Glycyrrhizin compared to placebo showed a reduction in the expression of ACE2 protein and gene, therefore reducing the uptake of COVID-19 at the cellular level and its spread. A significant main effect was detected in the MRNA ACE2 coding at the level of the small intestine (p = 0.04) [12].…”
Section: Chinese Herbal Medicinementioning
confidence: 97%
“…The top two herbs used were Radix astragali and Glycyrrhizae Radix Et Rhizoma [13]. Both are associated with having qi blood, a tonifying effect that replenishes the body when weak [12]. Individual case studies also tested the effectiveness of Shuanghuanglian oral liquid (SHL) (including honeysuckle, forsythia, and Scutellaria baicalensis).…”
Section: Chinese Herbal Medicinementioning
confidence: 99%
“…G. glabra and its active components have been shown promising results to combat SARS-CoV-2 infection and can be useful in treating patients with COVID-19 as on scientific evidences collected from some of the recently published reviews ( Bailly and Vergoten, 2020 ; Fatima et al, 2020 ; Huaccho-Rojas et al, 2020 ; Jezova et al, 2020 ; Murck, 2020 ; Srivastava et al, 2020 ; Adithya et al, 2021 ; Boozari and Hosseinzadeh, 2021 ; Jalali et al, 2021 ; Khan et al, 2021 ; Idrees et al, 2021 ; Brendler et al, 2021 ; Diomede et al, 2021 ; Liana and Phanumartwiwath, 2021 ; Malekmohammad et al, 2021 ; Merarchi et al, 2021 ). Several mechanisms have been identified and have been depicted in figure 4 .…”
Section: Potential Health Benefit Of G Glabra As Anti-inflammatory Antiviral and Immunomodulatory Agentsmentioning
confidence: 99%